Regulation of human dendritic cell immune functions by ion channels. (June 2018) - Vandier, Christophe; Velge-Roussel, Florence
Highlights: Human and murine DCs exhibit huge differences in ion channel involvements in its functions. Maturation of hDCs is mainly controlled by CRAC channels as Orai-1/STIM-1. KCa3.1 and P2X7 channels are involved in hDC migration. P2Y receptors controls intracellular calcium and inflammatory hDCs in normoxie. Abstract : Dendritic cells (DCs) are highly specialized antigen-presenting cells (APCs) able to induce both specific immunity and immune tolerance. Using information gathered from the tissue where they reside, DCs adjust their functional activity to ensure that protective immunity is favoured while unwanted or exaggerated immune responses are prevented. The remarkable ability of these cells to induce, enhance and orient the immune response, while at the same time maintaining self-tolerance, makes them key players in the immune system. Despite the fact that the role of Ca 2+ has been clearly established in human DC functions, the link between ion homeostasis, mainly Ca 2+, and DC functions is not fully understood. After all, a growing number of works clearly show the role of SOCE and associated channels in the maturation step, and those of K + channels in migration. This review highlights the key papers published over the past few years and summarizes prospects for the near future.